1995
DOI: 10.1016/s0022-5347(01)67534-7
|View full text |Cite
|
Sign up to set email alerts
|

Organ Preserving Surgery in Testicular Epidermoid Cysts

Abstract: Our experience with 18 patients with simple epidermoid cysts of the testis (monodermal teratoma) is reported. In all patients the tumor was enucleated completely and 2 biopsies of the adjacent parenchyma were obtained for exclusion of associated germ cell cancer, scar or carcinoma in situ. There was no evidence of malignancy in any biopsy specimen. Preoperative evaluation included physical examination, testicular sonography, and determination of alpha-fetoprotein and beta-human chorionic gonadotropin levels. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 45 publications
1
42
0
1
Order By: Relevance
“…First described in 1942 by Dockerty and Priestley (3), epidermoid cyst accounts for 1%-2% of all testicular lesions. The majority of patients are in the 2nd to 4th decades of life, although patient age ranges from 3 to 77 years (1,2,4). The reported cases have occurred in white and Asian persons.…”
Section: Discussionmentioning
confidence: 99%
“…First described in 1942 by Dockerty and Priestley (3), epidermoid cyst accounts for 1%-2% of all testicular lesions. The majority of patients are in the 2nd to 4th decades of life, although patient age ranges from 3 to 77 years (1,2,4). The reported cases have occurred in white and Asian persons.…”
Section: Discussionmentioning
confidence: 99%
“…epidermoid cysts have long been the ideal target for partial orchiectomy, being benign and often identified on ultrasonography owing to the fact they are cystic with little blood flow. Heidenreich et al 4 reported 100 patients with epidermoid cysts with 37-year follow-up; no patients experienced recurrence or distant metastases. leydig cell tumors are also essentially benign with only rare metastases.…”
Section: Management Of Benign Testicular Massesmentioning
confidence: 99%
“…3 In a large series of patients with GCT and a margin of normal testis around the tumor who underwent partial orchiectomy with meticulous spillage precautions, no seeding or carcinoma in situ (CIS) were detected. 4 CIS is the progenitor of testicular GCT and has a greater than 50% chance of progressing to a solid GCT. Furthermore, in recent years it has been recognized that benign lesions represent a significantly higher proportion of testicular masses than previously thought-approaching 50%-most probably owing to the increased use of high resolution ultrasonography that can detect smaller nonpalpable lesions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, testicular-sparing surgery has been successfully performed in cases where the preoperative likelihood of benign disease was high. 8,9 In patients with small, malignant germ cell tumors, testicular-sparing surgery coupled with local adjuvant therapy showed good oncologic control in most cases. 10 An intraoperative frozen-section examination can accurately diagnose testicular cancer, 9 and radical orchiectomy should be performed if an equivocal lesion is found.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 In patients with small, malignant germ cell tumors, testicular-sparing surgery coupled with local adjuvant therapy showed good oncologic control in most cases. 10 An intraoperative frozen-section examination can accurately diagnose testicular cancer, 9 and radical orchiectomy should be performed if an equivocal lesion is found. Because of the benign nature of testicular dermoid cysts, testis-sparing surgery can be attempted in young patients with a small tumor if the intraoperative frozen-section examination shows a benign lesion.…”
Section: Discussionmentioning
confidence: 99%